Kajian Interpolasi Dua Dimensi dalam Tabel Nilai Kritik Sebaran F Berbantuan Program Matlab - Irna Karlina Sensiana Blegur (Universitas Nusa Cendana, 2021)
The purposes of this research are to examine how to perform two-dimensional interpolation for determine the value of the F distribution, to make a two-dimensional interpolation program using Matlab and reviewing the comparison of the methods used (manually and program). This research was conducted by using literature study approach. The results of this research are: first, the two-dimensional interpolation in F distribution table can be done using the successive univariate polynomial interpolation. Two-dimensional interpolation formulas can be made by referring to the general form of Lagrange and Newton's interpolation polynomials. Second, a two-dimensional interpolation program assisted by Matlab that is a program that can determine the intermediate value of a function in two variables using the Lagrange and Newton’s polynomial interpolation formula has been created. Third, based on the final results, there is no difference shown by the two methods used. Judging from the process, two-dimensional interpolation using the Lagrange polynomial method has advantages in simplicity of programming, but requires a long time in manual completion. While the Newton polynomial interpolation method has advantages in the simplicity of the manual work process, but it requires a long time to make the program.